The Strength of Direct Ties: Evidence from the Electronic Game Industry - Jörg Claussen; Oliver Falck; Thorsten Grohsjean (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2011)
We analyze the economic effects of a developer's connectedness in the electronic game industry. Knowledge spillovers between developers are likely to be of special relevance in this knowledge-intensive and regionally concentrated industry. We calculate social network measures for a developer's connectedness to other developers at multiple points in time. In a regression in which we exploit within-career variation in social network measures, we find that the number of direct ties a developer has to other developers has a strong effect on both a game's revenues and critics' scores. The quality of indirect ties makes no additional contribution to the game's success.
urn:nbn:de:bvb:19-epub-12298-4
Keywords: 650; Computerspiel; Produktentwicklung; Erfolgsfaktor; Soziales Netzwerk; Wissenstransfer; Unterhaltungselektronische Industrie